Meningkatkan Keterampilan Menulis Tegak Bersambung pada Siswa Kelas 3 Sekolah Dasar dengan Metode Struktural Analitik Sintetik (SAS) - Hafizah Hanifah; Chandra Chandra; Inggria Kharisma (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to determine the effect of the Structural Analytic Synthetic (SAS) method on second-grade elementary students' ability to write in cursive. Writing, especially cursive writing, is an essential part of learning the Indonesian language at the elementary level. However, many students still struggle with this skill. The SAS method is believed to help students understand word structures step by step—from full sentences, words, syllables, to letters—thus making the writing process easier. This research uses a quantitative approach with a quasi-experimental design and a nonequivalent control group model. The sample consisted of two classes: the experimental class received treatment using the SAS method, while the control class used conventional methods. The instrument used was a cursive writing test (pretest and posttest), and data were analyzed using a t-test with the assistance of SPSS. The results show a significant difference between the posttest scores of the experimental and control groups, with a significance value of 0.000 < 0.05. This indicates that the use of the SAS method effectively improves the cursive writing skills of second-grade elementary students.